Research on telework in Slovenia - Jereb, Eva (Informatica (Ljubljana), 1999)
Although a lot of research on telework has been done, most of it has been carried out in USA and EC countries. Until today there have been no studies on telework in Slovenia. This paper presents the results of a study of telework in Slovenia carried out in 1997. The paper also compares telework between Slovenia and other European countries.
Keywords: delo na daljavo; pisarniško poslovanje; avtomatizacija